2011
DOI: 10.1007/s10856-011-4448-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Sr and H3PO4 concentration on the hydration of SrCaHA bone cement

Abstract: Sr-contained calcium hydroxyapatite (SrCaHA) cement is a potential biomaterial for in vivo bone repair and surgery fixation due to its excellent biodegradability, bioactivity, biocompatibility, easily shaping and self-hardening. We had ever reported the in vitro physiochemical properties, biocompatibility and in vivo degradability of the SrCaHA cement obtained by mixing a cement powder of Ca(4)(PO(4))(2)O/CaHPO(4)/SrHPO(4) and a cement liquid of diluted H(3)PO(4) aqueous solution. In the present study, we inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…83 In their TTCP/DCPA/DSPA cement system, Guo et al described a non-linear influence of Sr content on the mechanical properties: while an optimum composition was found at a Sr/(Sr + Ca) ratio of 0.05 with an increase of compressive strength up to 66 MPa compared to B50 MPa for the Sr-free reference cement, higher Sr content resulted in a reduced compressive strength. 83,84 A comparable optimum was described for DCPD-based cements where SrCO 3 replaced the second precursor component, CaO. 88 Here, up to 1.5% molar fraction of SrCO 3 increased the compressive strength of the set cement from B7 to B20 MPa.…”
Section: Mechanical Characteristics Of Srcpcmentioning
confidence: 67%
See 2 more Smart Citations
“…83 In their TTCP/DCPA/DSPA cement system, Guo et al described a non-linear influence of Sr content on the mechanical properties: while an optimum composition was found at a Sr/(Sr + Ca) ratio of 0.05 with an increase of compressive strength up to 66 MPa compared to B50 MPa for the Sr-free reference cement, higher Sr content resulted in a reduced compressive strength. 83,84 A comparable optimum was described for DCPD-based cements where SrCO 3 replaced the second precursor component, CaO. 88 Here, up to 1.5% molar fraction of SrCO 3 increased the compressive strength of the set cement from B7 to B20 MPa.…”
Section: Mechanical Characteristics Of Srcpcmentioning
confidence: 67%
“…For example, using the cementing reaction of DCPA/TTCP into hydroxyapatite upon mixing with phosphoric acid, DCPA can be substituted by its strontium analogue strontium hydrogen phosphate (SrHPO 4 , DSPA). In this way, Sr-substituted apatite cements with a Sr/(Sr + Ca) ratio of up to 0.1 were prepared by Guo et al 83,84 Since mixtures of DCPD and CaCO 3 can set into HA, one strategy to obtain SrHA cements is to replace CaCO 3 in the precursor by SrCO 3 . Following this approach, precursors composed of DCPD and various CaCO 3 -SrCO 3 mixtures were prepared by Tadier et al to obtain cements with up to 8 wt% Sr. 85 In contrast to the above-mentioned systems, the setting product was biphasic: the set cement was composed of a mixture of hydroxyapatite and SrCO 3 and no SrHA could be detected.…”
Section: Apatite-forming Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some previous studies, it was also reported that CaCO 3 , SrHPO 4 and Strontium Carbonate additions increased the mechanical properties. 26,28 It was shown that increasing the amount of Sr decreased the reactivity and higher strength was reported than that of the trabecular bone via the in vitro study. 29 It was also reported that the addition of SrCO 3 into calcium phosphate-based compounds increased the mechanical properties by precipitating the formation of the SrHA.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] A significant deal of attention has been paid to strontium containing hydroxyapatite cements to increase their bioactivity, biocompatibility and compressive strength. [10][11][12][13][14] The majority of previous studies devoted to the synthesis of SrHP have been focused on the hydrothermal method, 15,16 cathodic reduction 17 and solution growing. [18][19][20][21][22][23][24][25] Taher et al studied the hydrothermal synthesis of SrHP from a mixture of Li 2 CO 3 , SrCO 3 and H 3 PO 4 in water after conducting a thermal procedure at 180 1C for 6 h. 15 More recently, Zhang et al developed SrHP nano-belts without any surfactant as the template at 160 1C.…”
Section: àmentioning
confidence: 99%